2013
DOI: 10.1111/febs.12353
|View full text |Cite
|
Sign up to set email alerts
|

In the eye of the storm: mitochondrial damage during heart and brain ischaemia

Abstract: We review research investigating mitochondrial damage during heart and brain ischaemia, focusing on the mechanisms and consequences of ischaemia-induced and/or reperfusion-induced: (a) inhibition of mitochondrial respiratory complex I; (b) release of cytochrome c from mitochondria; (c) changes to mitochondrial phospholipids; and (d) nitric oxide inhibition of mitochondria. Heart ischaemia causes inhibition of cytochrome oxidase and complex I, release of cytochrome c, and induction of permeability transition an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 140 publications
2
66
0
1
Order By: Relevance
“…The reason for decline in state III respiration may be due to deficiency in supply of respiratory substrates. This may occur due to compromise of ETC components and oxygen to produce ATP (Borutaite et al 2013). Previous studies targeting mitochondrial dysfunction have shown a decrease in state III respiration following anoxia which is in agreement to our finding (Rosenberg et al 1989).…”
Section: Discussionsupporting
confidence: 93%
“…The reason for decline in state III respiration may be due to deficiency in supply of respiratory substrates. This may occur due to compromise of ETC components and oxygen to produce ATP (Borutaite et al 2013). Previous studies targeting mitochondrial dysfunction have shown a decrease in state III respiration following anoxia which is in agreement to our finding (Rosenberg et al 1989).…”
Section: Discussionsupporting
confidence: 93%
“…28 Complex I activity is suppressed during ischemia so enhancing its activity is a potential treatment strategy. 29,30 In this in vivo study, we found ketones improved mitochondrial complex I activity in the penumbra. To restore the mitochondrial function in the penumbra, ketones save it from irreversible damage as evidenced by the reduction in infarct volume.…”
Section: Discussionmentioning
confidence: 54%
“…Neuronal apoptosis has emerged as a key deleterious factor in cerebral ischemia and is a result of complex pathophysiological cascades (Balduini et al, 2012;Hofmeijer and van Putten, 2012;Wang et al, 2014). Nowadays it is well established that mitochondrial damage plays an important role in ischemia-induced neuronal apoptosis (Borutaite et al, 2013;Calo et al, 2013;Sanderson et al, 2013). Under ischemia condition, abnormal mitochondrial membrane permeabilization subsequently causes the down-regulation of mitochondrial membrane potential (MMP) and the release of cytochrome c from mitochondria into the cytoplasm, further activating downstream apoptosis pathway (Jordan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%